Pengembangan Media Pembelajaran Berhitung Smart Bottle Cup Pada Materi Penjumlahan Bersusun Untuk Siswa Sekolah Dasar - Amanda Gusti (Master Journal of Future Education, 2026)
This research was conducted at SDN 197/II Pulau Pekan, specifically in second grade. The background was difficulties in students' numeracy skills, and educators had not used learning media effectively. The arithmetic teaching aids used were limited to manual learning. Students appeared confused and struggled with calculations. The low student learning scores indicated that students were unable to learn to count using only their hands. It would be beneficial to provide learning media such as the Smart Bottle Cup. This research was a Research and Development (R&D) study using the Borg and Gall method, designed to assist learning media developers in creating appropriate products for educational needs. The results of the Smart Bottle Cup learning media study indicated its suitability for use as a learning tool in elementary schools. This was demonstrated by the validity assessments of experts (validators) consisting of material experts (80%), media experts (85%), language experts (80%), and instrument experts (80%). Practical results from three students and three teachers were used to determine the product's practicality. The results of the practicality questionnaire showed an average percentage of over 90%, which is considered very practical. This indicates that the Smart Bottle Cup learning media is valid and practical to use because it is easy to use, engaging, useful, and can support classroom learning.